Augmentation Plating Superior to Nail Exchange for Femoral Shaft Nonunion after Nail Fixation - Kuznar, Wayne (MD Conference Express, 2014)
The optimal treatment for femoral shaft nonunion after intramedullary nail fixation is controversial and is a challenge for orthopaedic surgeons. This article discusses a retrospective study comparing nail exchange with augmentation plating to treat femoral shaft nonunion after nail fixation.